Le Cordon Bleu Dessert Techniques - Duchenem Laurent; Jones, Bridget (New york William Morrow and company, 1999)
For the first time, the chefs and instructors of the world-renowned Le Cordon Bleu cooking schools have written a cookbook that will teach anyone, from novices with a sweet tooth to expert bakers, how to prepare beautiful and delicious desserts at home. Hundreds of techniques are explained in step-by-step detail, with more than one thousand color photographs illustrating the experts methods for success. Even if you've never made a sugar syrup or rolled out a piecrust before, this is the book for you. The simplest of techniques, typically left out of most cookbooks, are covered in the greatest detail. When you've mastered the basics, Le Cordon Bleu Dessert Techniques will challenge you to make increasingly difficult recipes on your way to preparing dazzling desserts. For example, upon mastering the basics of grating, chopping, melting, tempering and piping choclate, you'll want to try your hand at creating choclate ribbons and culs, marbleized chocolate slabs, and lacy chocolate cups for truly spectacular presentation. Once you've reviewed the techniquws for baking perfect cake layers, you'll be reday to creat a Chocolate Chestnut Roulade or the classic and decadent Sachertorte. After learning from the experts, you'll be piping meringue, whipping up chocolate mousse, and preparing Pots de Creme with ease before you know it.
- Fruit Desserts - Iced Desserts - Custards , Cream & Whips - Souffles , mousses & Meringues - Soft Cheese Desserts - Batters & Omelettes - Basic Techniques - Cakes &Gateaux -Pastries - Grains - Petits Fours - Finishing Touches
Keywords: Desserts